(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research paper investigates the perceptions and challenges faced by farmers amidst the evolution of modern agricultural practices in India. Employing a quantitative methodology, the study scrutinizes farmers’ perspectives towards adopting contemporary agricultural trends and their encounters with various impediments hindering the integration of these practices. Findings indicate a predominantly favorable attitude among farmers towards modern agricultural techniques, highlighting their potential to enhance crop yield, farm productivity, profitability, and overall farm management. However, juxtaposed against this positivity are significant barriers including limited access to resources and education, financial constraints, and inadequate support systems, posing substantial challenges to seamless adoption. These revelations underline the need for comprehensive interventions to empower farmers, fortify agricultural resilience, and propel socio-economic development in rural communities.